The life course effects of care - Justin van de Ven; Patryk Bronka; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2024)
Caring has its most obvious effects when it is actually required. Yet the effects of care are likely to extend to other periods of the life course. People may anticipate the need to provide informal care, either as part of their fertility decisions, or in response to deteriorating health of loved-ones. Similarly, a reason given for high savings rates among the elderly is the desire to self-insure against the needs consequent on adverse health shocks, including the need for (expensive) formal care. Furthermore, both informal care and incapacity demanding care can have effects that persist well after the actual episodes of care are past, for example, due to labour market scarring and/or depleted savings. This study uses current best-practice methods of economic analysis to explore these phenomena. Focussing on the channels of employment and savings, the study considers how the effects of care vary over the life course, and with the time that episodes of care are encountered.
Keywords: 330; Poverty; Labour Market; Microsimulation; Older People; Life Course Analysis; Economics; Demography; Savings And Assets; Child Development; Disability; Caregiving